Google Trends and pollen concentrations in allergy and airway diseases in France. Issue 10 (28th July 2019) - Bousquet, Jean; Onorato, Gabrielle L.; Oliver, Gilles; Basagana, Xavier; Annesi‐Maesano, Isabella; Arnavielhe, Sylvie; Besancenot, Jean‐Pierre; Bosse, Isabelle; Bousquet, Philippe J.; André Charpin, Denis; Caillaud, D.; Demoly, Pascal; et al.
Abstract: Background: Google Trends (GTs) is a web‐based surveillance tool that explores the searching trends of specific queries via Google. This tool proposes to reflect the real‐life epidemiology of allergic rhinitis and asthma. However, the validation of GTs against pollen concentrations is missing at the country level. Objectives: In the present study, we used GTs (a) to compare the terms related to allergy in France, (b) to assess seasonal variations across the country for 5 years and (c) to compare GTs and pollen concentrations for 2016. Methods: Google Trends queries were initially searched to investigate the terms reflecting pollen and allergic diseases. 13‐ and 5‐year GTs were used in France. Then, 5‐year GTs were assessed in all metropolitan French regions to assess the seasonality of GTs. Finally, GTs were compared with pollen concentrations ( Réseau National de Surveillance en Aerobiology ) for 2016 in seven regions (GTs) and corresponding cities (pollen concentrations). Results: The combination of searches for "allergy" as a disease, "pollen" as a disease cause and "ragweed" as a plant was needed to fully assess the pollen season in France. "Asthma" did not show any seasonality. Using the 5‐year GTs, an annual and clear seasonality of queries was found in all regions depending on the predicted pollen exposure for spring and a summer peak but not for winter peaks. The agreement between GT queries and pollen concentrations is usually poor except for spring trees and grasses. Moreover, cypress pollens are insufficiently reported by GTs. Conclusions: Google Trends cannot predict the pollen season in France. Abstract : Google Trends (GTs) is a web‐based tool that explores searching trends. This tool was used to search the terms related to allergy in France, to assess 5‐year seasonal variations across the country and to compare GTs with the pollen concentrations for 2016. The combination of terms "allergy, " "pollen" and "ragweed" was needed to fully assess the pollen season in France. GTs cannot predict the pollen season in France.